Supervisory fault tolerant control of the GTM UAV using LPV methods - Péni, Tamás; Vanek, Bálint; Szabó, Zoltán; Bokor, József (Zielona Góra: Uniwersytet Zielonogórski)
A multi-level reconfiguration framework is proposed for fault tolerant control of over-actuated aerial vehicles, where the levels indicate how much authority is given to the reconfiguration task. On the lowest, first level the fault is accommodated by modifying only the actuator/sensor configuration, so the fault remains hidden from the baseline controller.
Keywords: fault tolerant control; linear parameter-varying systems; supervisory architecture; flight control